“I’m a Marvel Girl”: Exploration of the Selection Practices of Comic Book Readers - Serantes, Lucia Cedeira (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Based on Catherine Ross’ findings about avid readers, this study examines the way four comic book readers choose the graphic novels that they read for pleasure. Three major themes emerged from the analysis of the qualitative interviews: the diverse roles of comic book stores; the connection with other media formats; and the accessibility of the format. Fondée sur les données recueillies par Catherine Ross concernant les lecteurs avides, cette étude examine de quelle façon quatre lecteurs de bande dessinées (comic books) choisissent les bande dessinées romanesques (graphic novels) qu'ils désirent lire par plaisir. Trois grands thèmes ressortent de l'analyse des entrevues qualitatives : les divers rôles des détaillants de bandes dessinées, le contact avec d'autres formes médiatiques et l'accessibilité du format. <div style="font-size: 14.72px; font-family: sans-serif; left: 390.881px; top: 298.24px; transform: scale(0.91824, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-font-name="g_font_p0_2" data-canvas-width="3.672958474159241">